2013
DOI: 10.1017/s1368980013001080
|View full text |Cite
|
Sign up to set email alerts
|

Severe malnutrition among children under the age of 5 years admitted to a rural district hospital in southern Mozambique

Abstract: Objective: To describe the burden, clinical characteristics and prognostic factors of severe malnutrition in children under the age of 5 years. Design: Retrospective study of hospital-based data systematically collected from January 2001 to December 2010. Setting: Rural Mozambican district hospital. Subjects: All children aged ,5 years admitted with severe malnutrition. Results: During the 10-year long study surveillance, 274 813 children belonging to Manhiça's Demographic Surveillance System were seen at out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 28 publications
(31 reference statements)
6
54
1
Order By: Relevance
“…The association between mortality and these factors has not been properly described in the literature, but it is likely that edema is associated with kwashiorkor (protein-deficient malnutrition) and oral candidiasis is a proxy of HIV coinfection, highly endemic in the Manhiça area 22 and highly prevalent among malnourished patients. 13 Regarding hyperglycemia, we found a prevalence of 1.7%, and a significantly higher associated CFR (12.1%, P < 0.001) when compared with normoglycemia. Other studies in similar settings have shown similar 7 or higher 8,44 prevalence rates.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The association between mortality and these factors has not been properly described in the literature, but it is likely that edema is associated with kwashiorkor (protein-deficient malnutrition) and oral candidiasis is a proxy of HIV coinfection, highly endemic in the Manhiça area 22 and highly prevalent among malnourished patients. 13 Regarding hyperglycemia, we found a prevalence of 1.7%, and a significantly higher associated CFR (12.1%, P < 0.001) when compared with normoglycemia. Other studies in similar settings have shown similar 7 or higher 8,44 prevalence rates.…”
Section: Discussionmentioning
confidence: 54%
“…11,13,41 In malnourished patients, glucose homeostasis 41 can be compromised in several ways, including a lack of exogenous nutritional intake, decreased absorption of disaccharides because of intestinal villous atrophy, increased oxidative stress, or glucose uptake compromised by intestinal bacteria. In our series, 62% of all hypoglycemic children were malnourished, with 19.4% being severely malnourished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, the <5yr mortality rate was 70/1000 live births. Severe malnutrition is common with an estimated IR of 35/1000 person-years among children from 1-2yr 15 .…”
Section: Settingmentioning
confidence: 99%
“…Research findings from several regions of the world are included; i.e. Africa: Senegal (3) , Uganda (4,5) , Mozambique (6,7) , Mali (8) , Sudan (9) , Kenya (10)(11)(12)(13) and South Sudan (14) ; Asia: Philippines, Malaysia and Indonesia (15) , India (16)(17)(18) , Pakistan (19) and Sri Lanka (20) ; the Caribbean: Trinidad and Tobago (21) ; and Latin America: Colombia (22) . This research reflects the wide range of nutritional issues that low-and middle-income countries face, i.e.…”
mentioning
confidence: 99%